Variable Phonetic Phenomena in Arabic: A Historical-Phonological Analysis - Nurali Mavlanov (Indonesian Journal Publisher, 2025)
This article examines the variable phonetic phenomena in the Arabic language through a historical-phonological lens. It explores key processes such as vowel shifts, consonant assimilation, emphatic consonant articulation, and dialectal variations, tracing their evolution from pre-Islamic Arabic to modern dialects. Drawing on historical texts, including the Qur’an and pre-Islamic poetry, as well as contemporary linguistic studies, the article highlights how phonetic changes reflect both internal linguistic developments and external influences. Challenges in standardizing pronunciation across Arabic dialects and implications for modern linguistic studies are also discussed. The analysis underscores the dynamic nature of Arabic phonology and its significance in understanding the language’s historical and cultural evolution